Antipodal terrains created by the Rheasilvia basin forming impact on asteroid 4 Vesta. Issue 9 (18th September 2013) - Bowling, T. J.; Johnson, B. C.; Melosh, H. J.; Ivanov, B. A.; O'Brien, D. P.; Gaskell, R.; Marchi, S.
Abstract: [1] The Rheasilvia impact on asteroid 4 Vesta may have been sufficiently large to create disrupted terrains at the impact antipode. This paper investigates the amount of deformation expected at the Rheasilvia antipode using numerical models of sufficient resolution to directly observe terrain modification and material displacements following the arrival of impact stresses. We find that the magnitude and mode of deformation expected at the impact antipode is strongly dependent on both the sound speed and porosity of Vesta's mantle, as well as the strength of the Vestan core. In the case of low mantle porosities and high core strengths, we predict the existence of a topographic high (a peak) caused by the collection of spalled and uplifted material at the antipode. Observations by NASA's Dawn spacecraft cannot provide definite evidence that large amounts of deformation occurred at the Rheasilvia antipode, largely due to the presence of younger large impact craters in the region. However, a deficiency of small craters near the antipodal point suggests that some degree of deformation did occur. Key Points: The Rheasiliva forming impact may have disrupted terrain at its antipode Impact modeling predicts significant deformation at and near the impact antipode Observations reveal high topography and a lack of small craters at the antipode